Strategi Fundraising Wakaf Uang Melalui Peran Dakwah Kyai Kampung - Rinawati, Ika (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2023)
The imbalance that accurs between the projected acquisition of cash waqf, which is 3 trilion annually and the actual acquisition of cash waqf, which is 10 billion annually, has led to the emergence of research which states that the problem of low acquisition of cash waqf is caused by a lack of socialization of cash waqf, the lack of socialization of cash waqf occupies the percentage the largest is 36.3% among other problem factors, namely the lack of skill in managing cash waqf, technology and accountability. This research method is descriptive qualitative using a case study approach. Data was collected by means of interviews, observation and documentation. The data was analyzed by means of data reduction, data presentation and verification. The results of the study were classified into 3, namely first, before the da'wah activities of the village clerics, the community did not know cash waqf at all and had never made waqf because they did not understand the benefits and management models, second, the concept of da'wah used by village kyai in Turen in socializing cash waqf consists of da'wah methods (Al Hikmah Al mau'idza al khasanah and Al mujJadilah bi al lati hiya ahsan), da'wah media (lectures and question and answer), and da'wah strategies (recitation strategies, imperative strategies), third, after the clerics' da'wah activities villages, the level of public understanding of cash waqf has increased, people have begun to understand the benefits of waqf and its management. In terms of interest in waqf, the community is not ready to do waqf for several reasons, including: the large number of routine benefits that are participated in (weekly, monthly and yearly compensation), preferring to invest in NU coins, and not being able to afford it economically.